2011
DOI: 10.1161/hypertensionaha.111.173559
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Endothelial Growth Factor Receptor Inhibitor Sunitinib Causes a Preeclampsia-Like Syndrome With Activation of the Endothelin System

Abstract: Abstract-Angiogenesis inhibition is an established treatment for several tumor types. Unfortunately, this therapy is associated with adverse effects, including hypertension and renal toxicity, referred to as "preeclampsia." Recently, we demonstrated in patients and in rats that the multitarget tyrosine kinase inhibitor sunitinib induces a rise in blood pressure (BP), renal dysfunction, and proteinuria associated with activation of the endothelin system. In the current study we investigated the effects of sunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
82
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 38 publications
8
82
2
Order By: Relevance
“…We and others have demonstrated in rats that coadministration of an ET-1 receptor antagonist with an RTKI can largely or completely prevent the rise in MABP, suggesting that activation of the ET pathway plays an important role in the sunitinib-induced MABP rise. 11,12 These observations in rats are fully supported by the present findings in swine, because the sunitinib-induced increase in SVRi and MABP completely reversed to presunitinib values in response to acute administration of the ET A /ET B receptor blocker tezosentan.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We and others have demonstrated in rats that coadministration of an ET-1 receptor antagonist with an RTKI can largely or completely prevent the rise in MABP, suggesting that activation of the ET pathway plays an important role in the sunitinib-induced MABP rise. 11,12 These observations in rats are fully supported by the present findings in swine, because the sunitinib-induced increase in SVRi and MABP completely reversed to presunitinib values in response to acute administration of the ET A /ET B receptor blocker tezosentan.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, sunitinib treatment for 8 days was accompanied by a decreased urinary nitrate excretion in adult rats and in patients receiving various inhibitors of the VEGF pathway, and the RTKI vandetanib decreases systemic plasma nitrate/nitrite levels in treated patients. 8,12,38 Results of clinical studies using FMD of the brachial artery as an index of NO bioavailability are conflicting. In one study, administration of the RTKI telatinib 9 was associated with a decrease in FMD from 6.0% to 3.9%, whereas in another study administration of the RTKI vandetanib had no effect on FMD (12.0% before and 13.8% after vandetanib).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that renal cGMP excretion is reduced in rats with sunitinib‐induced hypertension,25, 26 which may be a consequence of low renal NO bioavailability 11, 16, 24. In keeping with this finding, the phosphodiesterase inhibitor sildenafil failed to attenuate the arterial pressure rise in sunitinib‐treated rats 26.…”
Section: Introductionmentioning
confidence: 76%
“…Renal NO X excretion is less in sunitinib‐treated rats than in controls,11, 16 which is indicative of reduced NO formation and availability 29. Oral nitrate supplementation has been shown to lower arterial pressure in humans30 and in rats 21, 22.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation